Health decision-making capacity and modern contraceptive utilization among sexually active women: Evidence from the 2014-2015 Chad Demographic and Health Survey - Kenneth Setorwu Adde; Edward Kwabena Ameyaw; Barbara Elorm Mottey; Mawulorm Akpeke; Roberta Mensima Amoah; Nafisatu Sulemana; Kwamena Sekyi Dickson (BMC, 2022)
Abstract Background Globally, there has been an increase in the percentage of women in their reproductive ages who need modern contraceptives for family planning. However, in Chad, use of modern contraceptive is still low (with prevalence of 7.7%) and this may be attributable to the annual increase in growth rate by 3.5%. Social, cultural, and religious norms have been identified to influence the decision-making abilities of women in sub-Saharan Africa concerning the use of modern contraceptives. The main aim of the study is to assess the association between the health decision-making capacities of women in Chad and the use of modern contraceptives. Methods The 2014-2015 Chad Demographic and Health Survey data involving women aged 15-49 were used for this study. A total of 4,113 women who were in sexual union with information on decision making, contraceptive use and other sociodemographic factors like age, education level, employment status, place of residence, wealth index, marital status, age at first sex, and parity were included in the study. Descriptive analysis and logistic regression were performed using STATA version 13. Results The prevalence of modern contraceptive use was 5.7%. Women who take health decisions with someone are more likely to use modern contraceptives than those who do not (aOR = 2.71; 95% CI = 1.41, 5.21). Education, ability to refuse sex and employment status were found to be associated with the use of modern contraceptives. Whereas those who reside in rural settings are less likely to use modern contraceptives, those who have at least primary education are more likely to use modern contraceptives. Neither age, marital status, nor first age at sex was found to be associated with the use of modern contraceptives. Conclusion Education of Chad women in reproductive age on the importance of the use of contraceptives will go a long way to foster the use of these. This is because the study has shown that when women make decisions with others, they are more likely to opt for the use of modern contraceptives and so a well-informed society will most likely have increased prevalence of modern contraceptive use. Plain language summary The use of modern contraceptives remains a pragmatic and cost-effective public health intervention for reducing maternal mortality, averting unintended pregnancy and controlling of rapid population growth, especially in developing countries. Although there has been an increase in the utilization of modern contraceptives globally, it is still low in Chad with a prevalence rate of 7.7%. This study assessed the association between the health decision-making capacities of women in Chad and the use of modern contraceptives. We used data from the 2014 − 2015 Chad Demographic and Health Survey. Our study involved 4,113 women who were in sexual union and with complete data on all variables of interest. We found the prevalence of modern contraceptive utilization at 5.7%. Level of education of women, women who can refuse sex and employment status were found to be significantly associated with the use of modern contraceptives. Whereas those who reside in rural settings are less likely to use modern contraceptives, those who have at least primary education are more likely to use modern contraceptives. Our study contributes to the efforts being made to increase the utilisation of modern contraceptives. There is a need to step up contraceptive education and improve adherence among Chad women in their reproductive years. In the development of interventions aiming at promoting contraceptive use, significant others such as partners and persons who make health decisions with or on behalf of women must be targeted as well.